Creep behaviour of graphite oxide nanoplates embedded glass fiber/epoxy composites: Emphasizing the role of temperature and stress. (November 2017) - Kumar Ghosh, Sohan; Prusty, Rajesh Kumar; Rathore, Dinesh Kumar; Ray, Bankim Chandra
Abstract: Graphene based nano-reinforcements have emerged as promising fillers in polymeric materials. The objective of the present article is to elucidate the reinforcement effect of graphite oxide nanoplates (GONP) on the thermal, flexural and creep performance of glass fiber/epoxy (GE) composites. Thermal analyses by DSC, DMA and TGA showed reduced glass transition temperature of GE composite due to GONP incorporation, whereas no significant impact has been observed on the decomposition temperature. GONP addition has been found to be beneficial on the flexural properties of GE composite. To understand the effect of temperature on long-term mechanical durability, creep tests have been performed at various temperatures (50, 80 and 110 °C). Further, elevated temperature creep behaviour has been assessed at various stresses (10, 20 and 40 MPa) to comprehend the combined effect of temperature and stress. Improved creep resistance has been observed in GONP modified GE composites at relatively lower temperature and stress.